Estrategias pedagógicas mediadas por las TIC para el fortalecimiento de la convivencia escolar de los estudiantes (2018)
The use of new technologies in daily life requires a change of mentality in school organization and didactics, the incorporation of active and collaborative methodologies in the classroom, together with an adequate variety of tools that adapt to the reality of educational institutions, it allows the use of technologies in the teaching-learning process and they are facilitators of a good school coexistence. It is proposed to develop pedagogical strategies mediated by the ICT for the strengthening of the school coexistence of the 8th students of the Brooks Hill Bilingual School Educational Institution and to identify the state of the interpersonal relationships of the students and to describe the effect that it has on the school coexistence. We worked under the interpretive paradigm under a mixed approach with explanatory descriptive research design and a correlational research scope, the results show the interpersonal relationships among the students, we observe that it has high and low, but we can perceive a climate of healthy coexistence, a proposal was implemented to determine multicultural relations and processes. It was developed based on four criteria and a set of varied communication strategies which were supported from the exploration of interactive scenarios, through ICT. With the use of technologies, the school climate has been improved, students share more in a calm environment, with less discussion and conflicts, creating opportunities for all in a line of equal value regardless of their culture or roots